2011
DOI: 10.2169/internalmedicine.50.5148
|View full text |Cite
|
Sign up to set email alerts
|

Immunoglobulin D-Lambda Type Multiple Myeloma Presenting with FDG-PET/CT Negative Bone Marrow Involvement

Abstract: We here report a rare case of a patient with IgD-lambda-positive multiple myeloma presenting with FDG-PET/CT negative bone marrow involvement. A 72-year-old man was admitted to our hospital for evaluation of a paravertebral tumor of the chest. Thoracotomy was performed and a histopathological evaluation of resected intrathoracic tumor demonstrated a plasmacytic neoplasma. Initially we thought that this case was a solitary plasmacytoma because there were no positive findings on postoperative FDG-PET/CT. However… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 10 publications
0
1
0
1
Order By: Relevance
“…According to Machida et al [37], FDG does not accumulate in bone marrow lesions of IgD-λ type MM, whereas Nakamoto et al [23] observed non-FDG avid myelomas other than IgD-λ type MM. Our study found no relationship between MM type and number of visible lesions regardless of which tracer was used.…”
Section: Discussionmentioning
confidence: 99%
“…According to Machida et al [37], FDG does not accumulate in bone marrow lesions of IgD-λ type MM, whereas Nakamoto et al [23] observed non-FDG avid myelomas other than IgD-λ type MM. Our study found no relationship between MM type and number of visible lesions regardless of which tracer was used.…”
Section: Discussionmentioning
confidence: 99%
“…En relación con las anormalidades citogenéticas, éstas son variables (3,11,13) y algunos de los pacientes pueden tener un cariotipo normal (8,13), aunque no se ha descrito el efecto que tienen en el pronóstico de los pacientes con mieloma secretor de IgD.…”
Section: Discussionunclassified